1996
DOI: 10.1007/s004360050182
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of mucosal ileal gamma-interferon response during cryptosporidiosis in immunocompetent neonatal mice

Abstract: The kinetics of serum and ileal interferon-gamma (IFN-gamma) content were determined during recovery from cryptosporidiosis in NMRI suckling mice. A total of 60 mice aged 4 days were inoculated by intragastric gavage with 10(4) cryptosporidia (n = 30) or phosphate-buffered saline (n = 30). Six animals per group were killed on days 0, 3, 6, 9 and 13 postinoculation. Blood samples and ileum were collected. Experimental infection was followed by a rise in parasite load in the ileum starting on day 3 postinfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…Furthermore, it is noteworthy that prolonged exposure to IFNc down-regulates Na + -coupled glucose absorption in T84 cells (Yoo et al 2000) and the activity of brush-border membrane Na + /H + exchangers (NHE2, NHE3) in Caco-2 cells and rat intestine (Rocha et al 2001). Such a mucosal secretion of IFNc is known to occur during experimental cryptosporidiosis in our model, its kinetics being similar to those of oocyst excretion (Kapel et al 1996). We can therefore hypothesize that the intestinal absorption of all essential and non-essential amino acids transported through a Na + -dependent pathway may be downregulated during acute cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, it is noteworthy that prolonged exposure to IFNc down-regulates Na + -coupled glucose absorption in T84 cells (Yoo et al 2000) and the activity of brush-border membrane Na + /H + exchangers (NHE2, NHE3) in Caco-2 cells and rat intestine (Rocha et al 2001). Such a mucosal secretion of IFNc is known to occur during experimental cryptosporidiosis in our model, its kinetics being similar to those of oocyst excretion (Kapel et al 1996). We can therefore hypothesize that the intestinal absorption of all essential and non-essential amino acids transported through a Na + -dependent pathway may be downregulated during acute cryptosporidiosis.…”
Section: Discussionmentioning
confidence: 57%
“…It had previously been shown that IFN-␥ expression was increased in the terminal ileum as early as 3 days after C. parvum infection (14). Earlier expression of IFN-␥, well prior to the onset of adaptive immunity, has not been reported.…”
Section: Resistance To and Control Of Cryptosporidium Parvum Infectiomentioning
confidence: 96%
“…Mucosal immune response, especially IFNγ secretion, is known to play a key role in resistance to C. parvum infection (Ungar et al 1991;Chen et al 1993;Kapel et al 1996;You and Mead 1998). A type 2 response involving IL4 and IL10 has been more recently related to parasite clearance (Lacroix et al 2001).…”
Section: Introductionmentioning
confidence: 97%